'Innovation' in health care coverage decisions: All talk and no substance?. (January 2013) - Bryan, Stirling; Lee1, Helen; Mitton, Craig
There has been much discussion recently about 'innovation', or more precisely the lack of it, in pharmaceuticals and devices in health care. The concern has been expressed by national guideline bodies, such as the Common Drugs Review in Canada and the National Institute for Health& Clinical Excellence in the UK, applying strict cost-effectiveness criteria in their decision-making and, therefore, failing adequately to recognize the full benefits that come from innovation. In order to explore the legitimacy of such claims, we first define innovation, and second, explore the basis for assuming an independent and separable social value associated with innovation. We conclude that demands relating to innovation, such as relaxation of thresholds and premium prices for innovatory products, remain hollow until we have a compelling case on the demand side for a separable social value on 'innovation'. We see no such case currently.